Storage duration effect on deformation recovery of repacked alginates - Siti Sunarintyas; Dyah Irnawati (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Manufacturers supply alginate impression materials as a powder that is packaged in bulk and in individual container. Some Indonesian dental suppliers often repackage the bulk alginate into individual plastic packages which are not tied tightly and stored in the display room without air conditioner. It is known that critical factors to the shelf life of alginate includer avoidance of moisture contamination which may lead to premature setting of the alginate and avoidance of high temperature which may cause depolymerization of the alginate. Purpose: The aim of this study was to determine storage duration effect of repacked alginates on deformation recovery. Methods: Two brands of alginates (Tulip®TU, and Aroma Fine DF III®AF) were repacked into 120 plastic containers. The samples were stored in room condition (temperature 29° C ± 1° C, relative humidity 60% ± 10%) for 1, 2, 3, 4 and 5 weeks. The alginates setting time and recovery from deformation were measured according to the ANSI/ADA specification number 18 (ISO 1563). result: The results revealed that there was decreased setting time during 5 weeks but there was slight decreased in deformation recovery after 3 weeks storage. The ANOVA showed there was no significant difference of alginates deformation recovery among the storage times (p > 0.05). Conclusion: Storage duration of repacked alginates in plastic containers during 5 weeks in room condition do not influence the alginate deformation recovery.